A Novel Group Therapy for Children With ADHD and Severe Mood Dysregulation. (August 2013) - Waxmonsky, James G.; Wymbs, Fran A.; Pariseau, Meaghan E.; Belin, Peter J.; Waschbusch, Daniel A.; Babocsai, Lysett; Fabiano, Gregory A.; Akinnusi, Opeolowa O.; Haak, Jenifer L.; Pelham, William E.
Objective: No psychosocial treatments have been developed for children with ADHD and severe mood dysregulation (SMD) despite the significant prevalence and morbidity of this combination. Therefore, the authors developed a novel treatment program for children with ADHD and SMD.Method: The novel therapy program integrates components of cognitive-behavioral therapies for affect regulation with a parent-training intervention for managing recurrent defiant behaviors. It consists of nine 105-min child and parent groups run in unison. A pilot trial was conducted with seven participants with ADHD and SMD ages 7 to 12 who were on a stable stimulant regimen.Results : Six of the seven (86%) families completed the program. Participants showed large improvements in depressive symptoms, mood lability, and global functioning. Milder improvements in externalizing behaviors were observed.Conclusion: Results suggest the feasibility and potential efficacy of the therapy program for children with ADHD and SMD and warrant a larger controlled trial.